Raman Red‐Shift Compressor: A Simple Approach for Scaling the High Harmonic Generation Cut‐Off. Issue 11 (21st September 2021) - Légaré, Katherine; Safaei, Reza; Barrette, Guillaume; Arias, Loïc; Lassonde, Philippe; Ibrahim, Heide; Vodungbo, Boris; Jal, Emmanuelle; Lüning, Jan; Jaouen, Nicolas; Tao, Zhensheng; Baltuška, Andrius; et al.
Abstract : The use of ultrashort laser pulses with long wavelengths as drivers is a relevant strategy for scaling high harmonic generation (HHG) to higher photon energies. Here, stimulated Raman scattering enhanced by the formation of multidimensional solitary states in a molecular gas‐filled hollow‐core fiber as the mechanism to produce a versatile HHG driver is reported on. This recently discovered method allows to red shift and to compress conventional subpicosecond laser pulses with a simple experimental apparatus, ultimately increasing the generated photon energy, while assuring a high photon flux. The adaptability, simplicity, and stability of this method make it attractive for tailoring HHG sources to individual applications at specific photon energies. Measurements of resonant magnetic scattering in a cobalt/platinum multilayer sample are presented as a demonstration of the relevance of this approach for photon‐hungry applications in the extreme ultraviolet. Abstract : Multidimensional solitary states created during the stimulated Raman scattering process in gas‐filled hollow‐core fibers are proposed as a red‐shifted source of few‐cycle pulses for driving the high harmonic generation process. The resulting high‐flux source of photons in the extreme ultraviolet range is used to probe the magnetic properties of a cobalt/platinum multilayer sample through resonant magnetic scattering measurements.